2017
DOI: 10.1093/treephys/tpx098
|View full text |Cite
|
Sign up to set email alerts
|

The gall wasp Leptocybe invasa (Hymenoptera: Eulophidae) stimulates different chemical and phytohormone responses in two Eucalyptus varieties that vary in susceptibility to galling

Abstract: Gall-inducing insects produce various types of galls on plants, but little is known about the gall-induction mechanism of these galling insects. The gall wasp Leptocybe invasa Fisher & LaSalle (Hymenoptera: Eulophidae) forms galls of different sizes on several Eucalyptus species. To clarify the physiological responses of Eucalyptus to L. invasa infestation, we measured the dynamics of nitrogen (N), carbon (C), total phenolics, total tannins and four types of phytohormones (zeatin [Z] + zeatin riboside [ZR], gi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
22
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 55 publications
5
22
0
Order By: Relevance
“…Other authors have also reported differences in the concentrations of certain secondary compounds as well as certain types of phytohormones in plant gall tissue (Kraus & Spiteller, 1997;Pinkwart, Diettrich, & Luckner, 1998). Kot et al (2017), Li et al (2017) and Hall et al (2017) demonstrated that galls induced by cynipid species and the wasp Leptocybe invasa (Hymenoptera: Eulophidae), respectively, contain high levels of phenolic compounds compared with control tissues. Moreover, increased production of waxes in the gall induced by the insect Baccharopelma spp.…”
Section: Insect-induced Plant Galls and Phytochemistrymentioning
confidence: 94%
See 3 more Smart Citations
“…Other authors have also reported differences in the concentrations of certain secondary compounds as well as certain types of phytohormones in plant gall tissue (Kraus & Spiteller, 1997;Pinkwart, Diettrich, & Luckner, 1998). Kot et al (2017), Li et al (2017) and Hall et al (2017) demonstrated that galls induced by cynipid species and the wasp Leptocybe invasa (Hymenoptera: Eulophidae), respectively, contain high levels of phenolic compounds compared with control tissues. Moreover, increased production of waxes in the gall induced by the insect Baccharopelma spp.…”
Section: Insect-induced Plant Galls and Phytochemistrymentioning
confidence: 94%
“…Research conducted on galls of different species of plants have revealed that the composition and concentration of chemical substances in these structures can differ from those of other plant tissues and organs Saltzmann et al, 2008;Giron & Huguet, 2011;Huang et al, 2015;Oates et al, 2015;Hall, Carrol, & Kitching, 2017;Kot, Jakubczyk, Karaś, & Złotek, 2017). Tissues near the outside of the gall frequently accumulate high levels of tannins and other chemical compounds related to the process of defense of the gall and, in consequence, of the insect (Ananthakrishnan, 1998;Li et al, 2017;Chen et al, 2018;Nogueira et al, 2018). A study by Vereecke et al (1997) revealed that the chemical composition of ethanol and aqueous extracts of galls produced in the leaves of Nicotiana tabacum differs drastically from that of non-infected plant tissue extracts.…”
Section: Insect-induced Plant Galls and Phytochemistrymentioning
confidence: 99%
See 2 more Smart Citations
“…33,50 Thus, the different developmental gall stages and plant genotypes show that the gall-plant interaction is a synergistic process. 73,74 Additionally, the phenological association between plant and galling organism life cycles represents a new frontier of chemical ecology, which determines how the VOCs released during the host plant phenological stages interact with the galling insects, natural enemies or host plant interactors such as pollinators.…”
Section: The Ecological Role Of Gall-emitted Volatiles As Cues For Sumentioning
confidence: 99%